Multinodular goitre is a gateway for molecular testing of DICER1 syndrome. (13th September 2019) - Oliver‐Petit, Isabelle; Bertozzi, Anne‐Isabelle; Grunenwald, Solange; Gambart, Marion; Pigeon‐Kerchiche, Patricia; Sadoul, Jean‐Louis; Caron, Philippe J.; Savagner, Frédérique
Abstract: Background: DICER1 syndrome is an autosomal dominant disorder that predisposes individuals to develop benign or malignant tumours from infancy to adulthood. There is low‐to‐moderate penetrance of tumour development, which is sex‐ and age‐dependent. Multinodular goitre (MNG) is among the most highly penetrant phenotype of the disorder, especially in females. Patients and Methods: We report a series of eight families referred for childhood‐onset of MNG or DICER1‐related tumours with familial history of MNG in relatives. No additional families with these criteria stated were identified during the same date. We screened DNA samples from the probands and members of their family (40) for constitutional DICER1 variants using Next Generation Sequencing tools. Results: Germline pathogenic DICER1 gene variants were identified in all probands and several of their relatives: 64% presented with MNG/thyroidectomy as the phenotypic expression of the syndrome. DICER1 gene variants were identified in the RNAseIII and the PAZ domains. All tumour tissues studied presented clonal pathogenic variants in hotspot regions. Early identification of DICER1 variant carriers has permitted diagnosis and therapeutic scheme correction for two patients and cascade testing in relatives. Conclusions: Multinodular goitre is uncommon in children. Childhood‐onset MNG, multiple occurrences of the disease within the same family, or its association with rare benign or malignant tumours should raise suspicions of anomalies in the DICER1 gene, as proposed by recent international recommendations. Early detection of DICER1 pathogenic variants has important consequences in terms of therapeutic strategy, early tumour screening, and genetic counselling.